Kepentingan Kazakhstan atas Jalur Northern Distribution Network Tahun 2009-2015 - Chandra, Ida Ayu Ardha; Sushanti, Sukma; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT Territorial integrity is of paramount to a state. It is an absolute interest needed to be guarded at all cost. However, Kazakhstan agreed to support The Northern Distribution Network (NDN) and allowed US troops crossing its territory. This was done amidst existing pressures from Kazakh's two great power neighbors, Russia and China. Both states are knowingly giving potential security threats to Kazakhstan. This qualitative research analyzes the interest of Kazakhstan behind its support toward NDN access. Using Balance of Threats and National Interest concept, the research finds that Kazakhstan's border was no longer rigid as it faced far more beneficial interests both in economic and security. This suggested that guarding territorial integrity was not that absolute, at least in the context of Kazakhstan's multi-vector policy.   Keywords:         Northern Distribution Network, balance of threat, multi-vector policy